KAJIAN PENGELOLAAN LAHAN BERDASARKAN TINGKAT BAHAYA EROSI DAN POLA KONSERVASI TANAH DAN AIR DI DESA NGADIPIRO KECAMATAN NGUNTORONADI, KABUPATEN WONOGIRI - Sumarno Sumarno; Joko Winarno; Irawan Prastomo (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Land Management Study Based on The Degree of Erosion Hazard and Water and Soil Conservation Pattern in Ngadipiro, Nguntoronadi, Wonogiri. This research is aimed to identify the land management which has been done in Ngadipiro in order to overcome the erosion problem, to know and to analyze the class of erosion hazard, to get a soil and water conservation technique alternative which are appropriate to the this surrounding. This research is phenomenological qualitative descriptive research where the variable approach is done by field survey. The field unit map is got by pilling up on one another the map of the field use, soil depth and the declivity of the slope. The sample is taken by purposive sampling technique. Data and information about field management is got by analyzing directly to the field and by interviewing the informant key. Data analysis of the erosion prediction erosion hazard degree is done by using the formula of USLE. The result of the research shows that the erosion danger degree can be classified in to 5 class, they are: very light (SPL 4), light (SPL 3), medium (SPL 5), heavy (SPL 2, 6, 8, and 10), very heavy (SPL 1, 7, 9, 11, and 12), erosion that happenes in the field research (190,08 ton/ha/year/land units) has already been dangerous for the soil productivity preservation because it is already in the limit which is allowed (16,05 ton/ha/year/land units). The recommended soil and water conservations are: a) mechanical water and soil conservation: making the construction bench terrace in SPL 1, 5, 6, 7, 8, 9, 10, and 12, making rorak in SPL 2, 3, 4, 6, 7, 10, and 12, b) vegetative soil and water conservation technique: application agroforestry system by path planting in SPL 6, 7, 10, and 12, the use of soil covering plant in every SPL, for most in SPL 11, c) fertilizing as means to improve ingredients organic matter of land in every SPL. Keywords: Erosion hazard degree, land management, soil and water conservation